Weight regain in association with macronutrient diet composition and quality of life in women at least 5 years after bariatric surgery - Damin, Denise [UNESP]; Beato, Gabriel [UNESP]; Crisp, Alex; Junior, Irineu; Weber, Thabata [UNESP]; Oliveira, Maria Rita [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2021)
Bariatric surgery has been shown to be the best alternative for the control of severe obesity, with improvements in patient quality of life. However, regaining weight due to inadequate nutrition can compromise surgery results. Objective: to inves-tigate the relationship between weight gain and food consumption and quality of life among women at least 5 years after gastric bypass procedure. Methods: Seventy-three women who had bariatric surgery >= 5 years prior were evaluated for food consumption on 3 non-consecutive days and quality of life according to the dimensions of the BAROS tool. Results: Twenty two (29.7%) regained at least 10% of their weight. The group of women with stable weight loss had significantly lower carbohydrate consumption and showed no difference in energy consumption. Self-esteem and willingness to work also had a better score in this group, which contributed to a better quality of life score. Conclusion: From a weight regain below 10% after 5 years of bariatric surgery, the perception of quality of life among women changes. There are reasons for further studies on the effects of the proportion of macronutrients on dietary energy after bariatric surgery, including variations in the surgical technique and metabolic and anatomical variables.
Recuperación de peso en asociación con la composición de la dieta de macronutrientes y la calidad de vida en mujeres con al menos 5 años después de la cirugía bariátrica
Keywords: Bariatric surgery; Food consumption; Macronutrients; Quality of life